2006
DOI: 10.1111/j.1600-0528.2006.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

German short forms of the Oral Health Impact Profile

Abstract: Sufficient discriminative and evaluative psychometric properties of short forms of the OHIP-G make the instruments suitable to assess OHRQoL in cross-sectional as well as longitudinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
242
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(269 citation statements)
references
References 25 publications
19
242
0
8
Order By: Relevance
“…[25][26][27] Reissmann et al 2 used the RDC-TMD as a diagnostic tool and found that patients with myofascial pain exhibited a greater impact on quality of life than the other groups according to the OHIP questionnaire. However, the present results demonstrated that quality of life was associated with Group II of RDC-TMD and showed a stronger association with disc displacement with reduction ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Reissmann et al 2 used the RDC-TMD as a diagnostic tool and found that patients with myofascial pain exhibited a greater impact on quality of life than the other groups according to the OHIP questionnaire. However, the present results demonstrated that quality of life was associated with Group II of RDC-TMD and showed a stronger association with disc displacement with reduction ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although OHIP is a comprehensive and useful instrument, it is a long questionnaire with 49 items. Slade (26) derived and validated a short-form OHIP, which has been widely used in many studies (18,(27)(28)(29)(30)(31). In the Czech Republic, an oral health-related quality of life instrument currently does not exist.…”
Section: Questionnairementioning
confidence: 99%
“…The reduced version of this instrument, the OHIP-14, was developed by Slade in 1997, and validated for use in an elderly population in Australia 5 , and in an adult population in England 6 and Scotland 7 . Furthermore, it was translated and trans-culturally adapted in ten languages 8,9,10,11,12,13,14,15,16,17 , including Portuguese 12 . Its validation however, was tested specially on elderly individuals and urban populations, and its use has not been validated for rural populations speaking Latin languages.…”
Section: Introductionmentioning
confidence: 99%